Site‐specific impacts of a major hurricane on alpha and beta diversity in tropical forest seedling communities. Issue 7 (16th July 2021) - Worthy, Samantha J.; Rubio, Vanessa E.; Staiger, Kirstin; Ngouajio, Boris; Yang, Jie; Swenson, Nathan G.
Abstract: Large scale disturbances are known to impact the alpha and beta diversity of communities. However, whether these disturbances increase or decrease diversity is often debated. The goal of this study was to quantify how the diversity of the seedling community was impacted within and across elevation in the El Yunque forest of Puerto Rico following a major hurricane. We tested two alternative hypotheses, that hurricanes are relatively more homogenizing or non‐homogenizing forces, by quantifying changes in alpha and beta diversity of the seedling community post‐hurricane. This approach highlights whether ecological mechanisms associated with community homogenization (species‐specific survival, successional processes, and reduced environmental heterogeneity) or non‐homogenization (resource release, increased environmental heterogeneity, and stochastic processes) structure the seedling community post‐hurricane. We compared species richness, Fisher's α, Simpson's evenness, and multiple aspects of beta diversity within and among 25 seedling plots at 300, 400, and 500 m in elevation pre‐ and post‐hurricane. We found that species richness, diversity, and evenness were higher post‐hurricane, but abundance decreased 19%. Increases in alpha diversity suggest that hurricanes are non‐homogenizing forces potentially linked with increases in light levels promoting colonization of early‐successional species and resource release for other light‐demanding species. The beta diversity results varied in their support for hurricanes as homogenizing depending upon the spatial scale of the analysis, potentially due to a combination of mechanisms including species‐specific survival and site‐specific differences. To fully grasp how the seedling community responds and recovers from disturbance, additional long‐term monitoring will be needed to allow insight into the future of species richness, abundance, and spatial and temporal changes in community composition.